Quality of Life and Nutrition During Pregnancy - Mirsanjari, Mitra (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
A communitys transition towards modernity and urbanization leads to lifestyle changes that influence an individuals health through modifications in physical activity and nutritional habits. Women of childbearing age, particularly during pregnancy require special attention with regards to nutrition because their health potentially affects the well being of the entire community beside herself and the fetus. The aim of this study was to explore the association between quality of life and the nutrition knowledge and dietary intake among a group of pregnant women in Malaysia. A cross sectional survey was carried out to explore the association of knowledge, attitudes and healthy nutritional practices with quality of life during the second and third trimester of pregnancy. In this study, nutritional habits during pregnancy were significantly associated with social functioning, vitality and physical functioning. A basic understanding of the influence a healthy lifestyle has on physical and emotional well being during pregnancy helps the mother and family members to have a positive attitude towards the need for healthy behaviors in regard to nutrition and physical activity. The findings of this study show the importance of nutritional intake and behavior with respect to their effects on dimensions of health quality.